Appointment Lead Time Policy Development to Improve Patient Access to Care - Huang, Yu-Li; Bach, Sarah M. (Applied Clinical Informatics, 2016)
Background Patient access to care has been a known and continuing struggle for many health care providers. In spite of appointment lead time policies set by government or clinics, the problem persists. Justification for how lead time policies are determined is lacking.Objectives This paper proposed a data-driven approach for how to best set feasible appointment target lead times given a clinic’s capacity and appointment requests.Methods The proposed approach reallocates patient visits to minimize the deviation between actual appointment lead time and a feasible target lead time. A step-by-step algorithm was presented and demonstrated for return visit (RV) and new patient (NP) types from a Pediatric clinic excluding planned visits such as well-child exam and the same day urgent appointments. The steps are: 1. Obtain appointment requests; 2. Initialize a target lead time; 3. Set up an initial schedule; 4. Check the feasibility based on appointment availability; 5. Adjust schedule backward to fill appointment slots earlier than the target; 6. Adjust schedule forward for appointments not able to be scheduled earlier or on target to the later slots; 7. Trial different target lead times until the difference between earlier and later lead time is minimized.Results The results indicated a 59% lead time reduction for RVs and a 45% reduction for NPs. The lead time variation was reduced by 75% for both patient types. Additionally, the opportunity for the participating clinic to achieve their organization’s goal of a two-week lead time for RVs and a twoday lead time for NPs is discussed by adjusting capacity to increase one slot for NP and reduce one slot for RV.Conclusions The proposed approach and study findings may help clinics identify feasible appointment lead times.Citation: Huang Y, Bach SM. Appointment lead time policy development to improve patient access to care.
Keywords: Appointment; lead time; scheduling; patient access; policy